A Study on Teaching Applicable Mathematics in the Universities of Nepal - Panthi, Dinesh; Basnet, Ritu; Jha, K (Kathmandu University Journal of Science, Engineering and Technology, 2010)
The main objective of this paper is to analyze the program wise weightage of mathematics curriculum in universities of Nepal, in the areas of pure and applied mathematics. It also deals with the status of students' performance for mathematics at various levels. DOI: 10.3126/kuset.v4i1.2888 Kathmandu University Journal of Science, Engineering and Technology Vol.4, No.1, September 2008, pp 86-94